2011
DOI: 10.1007/s00253-011-3659-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance linked to residence time distribution by a novel wool-based bioreactor for tertiary sewage treatment

Abstract: Laboratory-scale experiments were carried out using up-flow 7 L Submerged Aerated Filter reactors packed with wool fibre or commercial plastic pall rings, Kaldnes, (70% by volume) support media for the tertiary treatment of sewage. The performance of the wool bioreactor was more consistent than that with Kaldnes medium, for both TOC removal (93%) and SS removal (90%). Both plastic and wool-packed bioreactors achieved complete nitrification at the load of about 0.4 kgCOD/m(3)/day. The sludge yield of the wool b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The WQSP showed higher porosity, larger surface area and lower bulk density, indicating better efficiency of wastewater treatment. Hu et al (2012) investigated the performance of aerated filter reactors using different media for tertiary sewage treatment. They demonstrated that submerged aerated filter reactors packed with wool fibre removed more organics (93%) and solids (90%) than did the reactors with commercial plastic pall rings.…”
Section: Packed Bed Biofilm Reactormentioning
confidence: 99%
“…The WQSP showed higher porosity, larger surface area and lower bulk density, indicating better efficiency of wastewater treatment. Hu et al (2012) investigated the performance of aerated filter reactors using different media for tertiary sewage treatment. They demonstrated that submerged aerated filter reactors packed with wool fibre removed more organics (93%) and solids (90%) than did the reactors with commercial plastic pall rings.…”
Section: Packed Bed Biofilm Reactormentioning
confidence: 99%
“…In fact, RTD experimental tests (Levenspiel, 1999), usually coupled to hydraulic models based on compartments such as the tank-in-series and the dispersion models, have been widely used for hydrodynamic analysis in wastewater treatment reactors. It was observed that mixing conditions (Hu et al 2012, Olive et al 2005, flow type and characteristics (Behzadian et al 2013, Autumn et al 2007, Gomez 2010, Ji et al 2012, Saragai et al 2010), dead volume (Autumn et al 2007, Hu et al 2012, Ji et al 2012, Sarathai et al 2010, channeling (Gómez 2010, Nemade et al 2010, Zeng et al 2005) and dispersal (Ji et al 2012, Nemade et al 2010, Zeng et al 2005 were observed as the most important characteristics. However, experimental RTD analysis techniques require a lot of time and resources.…”
Section: Introductionmentioning
confidence: 97%
“…Among various experimental methodologies, residence time distribution (RTD) is widely used to describe the phenomenon and liquid flow pattern not only of chemical reactors but also of biological reactors [4][5][6]. The RTD measurement is an effective tool that can help understanding and determining hydrodynamic parameters [7].…”
Section: Introductionmentioning
confidence: 99%